Analisis Komparatif Tutupan Mangrove Menggunakan Citra Landsat 9 dan Sentinel 2A di Desa Labuan Tereng Kabupaten Lombok Barat - Prasetyo, Andrie Ridzki; Valentino, Niechi; Hambali, Moh Rodiansyah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Labuan Tereng Village is a place where mangrove vegetation grows and develops. The location close to the harbor sheet makes the mangrove ecosystem damaged by port activities. High port activity can disrupt the condition of mangrove ecosystem development in Labuan Tereng Village. This study was conducted to evaluate mangrove health by looking at canopy cover or canopy density using the Hemispherical Photography method analyzed using Landsat 9 and Sentinel 2A to assess the extent of relationship between mangrove canopy cover and images. The findings revealed that the mean mangrove cover density value of 66% which is included in the medium category. Statistical analysis of several vegetation indexes with mangrove cover obtained the highest linear regression results in the SAVI model with a value of 0,41 for Landsat 9 images and 0,65 for Sentinel 2A images. The results of image data analysis on Sentinel 2A show a smaller pixel size value and contain more pixels so as to produce better and complex data analysis when compared to Landsat 9 imagery.